대한민국 고도비만 환자의 치료에 있어서 십이지장 치환술을 배제한 복강경하 위소매절제술의 조기 결과 - 한상문(Sang Moon Han); 김원우(Won Woo Kim) (Annals of surgical treatment and research, 2005)
Purpose: In Korea due to cultural background (food, life style) and environmental factors, type of obesity and previously defined operative indication is different from western country. Therefore, surgical procedure also must be applied differently under pattern of obesity. In this report we are trying to introduce our early results of laparoscopic sleeve gastrectomy without duodenal switch in Korean morbid obesity. Methods: We retrospectively reviewed 60 consecutive patients who underwent laparoscopic sleeve gastrectomy between January 2003 and May 2004. Four 12mm ports and one 15mm port are placed. The sleeve gastrectomy was done as routine fashion using ligasure and endo-GIA stapler to create a lesser curve gastric tube over 48 French bougie. Results: Excess weight loss was achieved in 71.6% during first six months postoperatively and 83.3% within 12 months. Body mass index (kg/cm2) was decreased average 9.2 during first 12 months postoperatively. Median weight loss at 12 months was 24.6 kg. Postoperative dyslipidemia was improved in 75% of patient within 12 months of operation. Diabetes as a co-morbidity was disappeared 100% of patient within 6 months postoperatively. Hypertension was disappeared in 92.9%, improved in 100% of patients within 12 months postoperatively. Arthritis and joint pain were improved 100% of patient within 12 months postoperatively. Weight loss plateaued at 12 months for the majority of patients. Conclusion: Additional studies and further follow up are needed to determine the best surgical treatment for Korean morbid obesity patient. However sleeve gastrectomy without duodenal switch operation can be an effective single weight loss procedure especially in Korea KCI Citation Count: 3